2007
DOI: 10.1007/s10661-007-9819-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity evaluation of water soil leachates by Ames test, comet assay, and preliminary Tradescantia micronucleus assay

Abstract: Combining genotoxicity/mutagenicity tests and physico-chemical methodologies can be useful for determining the potential genotoxic contaminants in soil samples. The aim of our study was to evaluate the genotoxicity of soil by applying an integrated physico-chemical-biological approach. Soil samples were collected at six sampling points in a Slovenian industrial and agricultural region where contamination by heavy metals and sulphur dioxide (SO(2)) are primarily caused by a nearby power plant. The in vitro alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…It appears that the addition of volumes up to 1000 µL is suitable for (geno)toxicity assessment of water. Our fi ndings for dump leachate and ground water are in accordance with several other studies (6,9,12,20,26,27). Sang et al (26) found cytogenetic damage in root tips of Hordeum vulgare exposed to municipal landfi ll leachate.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It appears that the addition of volumes up to 1000 µL is suitable for (geno)toxicity assessment of water. Our fi ndings for dump leachate and ground water are in accordance with several other studies (6,9,12,20,26,27). Sang et al (26) found cytogenetic damage in root tips of Hordeum vulgare exposed to municipal landfi ll leachate.…”
Section: Resultssupporting
confidence: 92%
“…The MN test is a well-known and validated endpoint that can predict increased cancer risk in a human population (22). This test has an advantage over tests with bacteria such as the Ames assay, which are not sensitive enough for water and soil leachate genotoxicity evaluations, especially when heavy metal contamination is anticipated (12,23). Nowadays the MN test is sometimes accompanied by counting apoptotic and necrotic cells, nuclear buds, and nucleoplasmic bridges (the cytome assay) (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This test, also known as Salmonella/microsome, consists, basically, in the employment of strains of the auxotrophic bacteria Salmonella typhimurium, i.e., deficient in the synthesis of the aminoacid histidine; the strains of these cells are unable to grow in minimum medium, where the mutagenic compounds are able to restore the synthesis capacity of this aminoacid, thus, the mutagenic expression corresponds to the growth of the colony in a minimum culture medium and it can be easily detected by counting the colonies (Umbuzeiro & Vargas, 2003). However, due to the low sensitivity of the Ames test for heavy metals, more studies should be directed to the development of bioassays with higher organisms (Gatehouse et al, 1990, as cited in Lah et al, 2008). Meristematic cells of A. cepa and V. faba, for example, constitute an effective cytogenetic material to analyze chromosome aberrations (figure 6) caused by soil pollution.…”
Section: Genotoxicity Biomarkersmentioning
confidence: 99%
“…as a result of disturbances in the mitotic spindle). Furthermore, it can be more sensitive than the bacterial Ames assay, especially when heavy metal contamination is anticipated (15,16). Recently, an inter-laboratory comparison study has also demonstrated that the in vitro micronucleus test is indeed very suitable for routine wastewater testing (17).…”
Section: Micronucleus Test and Proliferation Index (Pi)mentioning
confidence: 99%